The Effect of a Training Program Based on Mathematical Problem-Solving Strategies on Critical Thinking Among Seventh-Grade Students - Alfayez, Mona Qutaifan Ershed; Aladwan, Saida Quftan Abdelaziz; Shaheen, Hassan Rafi’ Ali (Frontiers in Education, 2022)
Aim: The present study aimed at investigating the effect of a training program based on mathematical problem-solving strategies on critical thinking skills among seventh grade students in King Abdullah II schools of Excellence. Method: The study adopted the quasi experimental research approach. The participants of the study comprised of 29 male seventh graders. The participants were distributed randomly into a control group (n=14) and an Interventional group (n=15). The study adopted the critical thinking skills test (75 items) developed by Abdul-Salam and Mamdouh (1982). The tests consisted of 5 sub-tests (Identifying assumptions, deduction, conclusion, interpretation and discussion). Intervention: the interventional training program was a group of training situations independent of the curriculum. These situations were based on the strategy of building an organized list or a table, the strategy of finding a pattern, trial and error strategy, the strategy of using an equation or a law, the strategy of building a model or a diagram, the strategy of solving an easier problem, deletion strategy, go backwards strategy, and logical justification strategy. Results: The results showed that there were significant statistical differences in the critical thinking post-test scores between the control group (M=26.5714, SD=3.95580) and the Interventional group (M=43.6667, SD=4.68534), (t=10.640, P=.000). Conclusion: the study concluded that training program based on mathematical problem-solving are effective interventional tool to improve the seventh graders’ critical thinking skills. The study recommends reviewing the content of the curricula designed for the elementary stage in Jordan and include drills related to mathematical problem-solving that aim to improve the critical thinking skills of the elementary stage students.